(untitled) (Research, Society and Development, 2021)
This article presents the protocol of a Scoping Review that aims to identify the recommendations proposed by public managers for the prevention and control of COVID-19 among the population deprived of liberty. The Scoping Review will include the following steps: identification of the research question; identification of relevant publications; selection of publications; data extraction; analysis and synthesis of evidence. The research question was formulated using the PCC acronym (population, concept and context): “What recommendations have been proposed by public managers for the prevention and control of COVID-19 among the population deprived of liberty in the prison system?”. Controlled and free vocabularies will be used for bibliographical search in the databases: EMBASE, Scopus, MEDLINE, Cinahl, Academic Search Premier, LILACS, Web of Science and Epistemonikos. After the searches, the data will be exported to Rayyan QCRI application, through which it will be possible to exclude duplicate publications and to proceed with the selection of publications by reading the titles and abstracts by two independent reviewers. Those who present the recommendations proposed for the prevention and control of COVID-19 among people deprived by public managers of health, justice and/or security and national and international institutions/agencies of liberty will be included. Preference will be given to experimental and quasi-experimental studies, analytical observational studies, case series, individual case reports, qualitative studies, opinion articles, commentaries and editorials. The publications included will be submitted to a narrative synthesis after extracting data from them, which will be conducted through the use of a specific form.